THE EFFECTIVENESS OFTHE OIL SPILL CONTINGENCY PLANCOMPLIANCES AMONG RELATED GOVERNMENT AUTHORITIES AT A PORT - Ismila Che Ishak; Nik Nabil Nabhan B Nik Kun (Marine Frontier, 2020)
The study attempts to evaluate the effectiveness of the current oil spill contingency plan concerning the response of oil spill cases on a port in Malaysia and, to explore the relationship of the viability on the current oil spill possibility arrange among the government-related specialists towards the oil spill cases. The oil spill contingency plan highlights the resources and the roles of the government agencies involved in the oil spill response. There are four independent variables in this study which elements of risk assessment, priorities for protection, strategic policy, and response techniques. The dependent variable of the study refersto the effectiveness of the oil spill contingency plan compliances among related government authorities at a port. 125 respondents have participated in this study, which wasfrom MMEA, DOE, Fisheries department, and Marine Department. The effectiveness of the oil spill contingency plan compliance is positively correlated with the response techniques, strategic policy, priorities for protection, and the risk assessment by 0.793, 0.791, 0.789, and 0.755 respectively. The collaboration from the related government agencies such as MMEA, DOE, Fisheries Department, and Marine Department in responding and controlling the oil spill incidents with the desired of the oil spill contingency plan at a port is vital. The role of the related government agencies is important to oil spill incidents.